Pengaruh Ekstrak etil Asetat dari Daun Sisik Naga (Pyrrosia piloselloides (L) Presl) terhadap Staphylococcus aureus - Arfiandi Arfiandi; Neri Fadjria; Dewi Nofita; Putri Nandinanti (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
The primary focus of this study revolves around the microbiological assessment of the effectiveness of ethyl acetate extract derived from Dragon's Scales Leaf (Pyrrosia piloselloides (L)) against Staphylococcus aureus. The employed method entailed the use of the diffusion technique with paper discs. The ethyl acetate extract of Dragon's Scales Leaf was formulated in three distinct concentrations, namely 40%, 60%, and 80%. In addition, Gentamicin at a 1% concentration served as the positive control. The measurements yielded inhibitory zone diameters of 14.05 mm, 15.49 mm, 14.90 mm, and 14.81 mm for the ethyl acetate extract and Gentamicin, respectively. This investigation's observed inhibitory zone diameters fall within the 'weak' category, with the highest extract concentration displaying a strength equivalent to Gentamicin as the positive control. In light of these findings, it can be concluded that the ethyl acetate extract of Dragon's Scales Leaf (Pyrrosia piloselloides (L)) can impede the growth of Staphylococcus aureus bacteria.